Progress and perspectives on pre-lithiation technologies for lithium ion capacitors. Issue 8 (2nd July 2020) - Jin, Liming; Shen, Chao; Shellikeri, Annadanesh; Wu, Qinag; Zheng, Junsheng; Andrei, Petru; Zhang, Ji-Guang; Zheng, Jim P.
Abstract : This review summarizes the progress of pre-lithiation technologies involving the fundamental research and practical application of LICs. Abstract : Lithium ion capacitors (LICs) can generally deliver higher energy density than supercapacitors (SCs) and have much higher power density and longer cycle life than lithium ion batteries (LIBs). Due to their great potential to bridge the gap between SCs and LIBs, LICs are becoming important electrochemical energy storage systems in the field of energy storage and conversion. Although it is generally accepted that pre-lithiation technologies are indispensable for the operation of LICs, no comprehensive overview of the existing pre-lithiation technologies has been conducted. In this progress report, we first classify LICs according to their energy storage mechanisms and discuss the multiple roles that the pre-lithiation technologies play for improving the performance of LICs. Then, we present the existing pre-lithiation methods used in LICs in detail and the current research progress is summarized. Finally, we provide a comprehensive comparison of the current pre-lithiation methods and propose the prospects and challenges of these methods from both a fundamental and a practical point of view. The broader impact of pre-lithiation technologies on next-generation LIBs is also discussed. This progress report aims at providing the fundamental knowledge necessary to researchers who are new to studying LICs and also serves as a guideline for senior researchers in the fields of LICs and LIBs for future research directions.